Proportions of Hypertension in Stable COPD Patients at the National Respiratory Center Persahabatan Hospital - Dewantoro, Luhur; Wiyono, Wiwien Heru; Yunus, Faisal; Agustin, Heidy; Damayanti, Triya; Antariksa, Budhi; Fachrucha, Fanny; Samoedro, Erlang; Elhidsi, Mia (Jurnal Respirologi Indonesia, 2024)
Background: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide. Most of these deaths are related to cardiovascular disease. This is due to systemic inflammation that causes increased vascular stiffness and hypertension. These comorbidities lead to poor quality of life, low exercise tolerance, and an increased risk of hospitalization. This study aims to report the proportion of hypertension among stable COPD patients in the Indonesian population.Methods: This cross-sectional study was conducted at the National Respiratory Center Persahabatan Hospital between February and March 2023. Stable COPD patients admitted to the Asthma and COPD Polyclinic who met the criteria were enrolled. Clinical information, vital signs, spirometry results, and DLCO measurements were collected.Results: There were 84 subjects participating in this study. The result of this study shows a 60.7% proportion of hypertension in stable COPD patients. Hypertension has a significant correlation with pulmonary functional values (P=0.021), severity degree of clinical COPD (P=0.004), Brinkman index (P=0.008), and age (P=0.0001). However, hypertension association with COPD duration (P=0.505) and DLCO (P=0.122) were not significant.Conclusion: The hypertension proportion in stable COPD Indonesian patients is 60.7%. Hypertension shows a significant association with pulmonary function values, severity degree of clinical COPD, Brinkman index, and age.